Do worsening lung ultrasound scans identify severe COVID-19 trajectories? - Blair, Paul W.; Hwang, Jimin; Pearce, Jackson; Fong, Tiffany C.; Cui, Erjia; Herrera, Phabiola; Liu, Gigi; Crainiceanu, Ciprian; Siddharthan, Trishul; Clark, Danielle V.; , The CCPSEI Research Team; Fenstermacher, Katherine; et al. (Frontiers in Medicine, 2022)
Background While point-of-care ultrasound (POCUS) has been used to track worsening COVID-19 disease it is unclear if there are dynamic differences between severity trajectories. Methods We studied 12-lung zone protocol scans from 244 participants [with repeat scans obtained in 3 days (N = 114), 7 days (N = 53), and weekly (N = 9)] ≥ 18 years of age hospitalized for COVID-19 pneumonia. Differences in mean lung ultrasound (LUS) scores and percent of lung fields with A-lines over time were compared between peak severity levels (as defined by the WHO clinical progression scale) using linear mixed-effects models. Results Mean LUS scores were elevated by 0.19 (p = 0.035) and A-lines were present in 14.7% fewer lung fields (p = 0.02) among those with ICU-level or fatal peak illness compared to less severe hospitalized illness, regardless of duration of illness. There were no differences between severity groups in the trajectories of mean LUS score 0.19 (p = 0.66) or percent A-lines (p = 0.40). Discussion Our results do not support the use of serial LUS scans to monitor COVID-19 disease progression among hospitalized adults.